2009
DOI: 10.1007/s10935-009-0167-y
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Participation in Group Parenting Education in an Australian Sample: The Role of Attitudes, Norms, and Control Factors

Abstract: We examined the theory of planned behavior (TPB) in predicting intentions to participate in group parenting education. One hundred and seventy-six parents (138 mothers and 38 fathers) with a child under 12 years completed TPB items assessing attitude, subjective norms, perceived behavioral control (PBC), and two additional social influence variables (self-identity and group norm). Regression analyses supported the TPB predictors of participation intentions with self-identity and group norm also significantly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 33 publications
2
23
1
10
Order By: Relevance
“…Therefore, a high level of social network ties may not serve a protective role in smoking among women. The result of this study is consistent with that of previous studies that have reported that poor social networks among women are associated with smoking behavior [47,49]. In addition, this finding provides evidence that it is necessary to sustain the optimal social network level not to smoke in women [49].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, a high level of social network ties may not serve a protective role in smoking among women. The result of this study is consistent with that of previous studies that have reported that poor social networks among women are associated with smoking behavior [47,49]. In addition, this finding provides evidence that it is necessary to sustain the optimal social network level not to smoke in women [49].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, smokers have a high degree of knowledge about the health risks of smoking, but a low will to quit smoking [46]. Positive social norm about smoking may be influenced by self-appraisal of benefit-harm on smoking, smoking acceptability within social network, delivering the misinformation by significant others, and so on [47,27]. Also, relatively low price of tobacco in Korea could be contributed to smoke in that make to improve the accessibility of social resource availability as part of social support [48].…”
Section: Discussionmentioning
confidence: 99%
“…Important referents often include legitimate authority figures (e.g., teachers) or peers who socially validate the behavior (Cialdini, 2001). For example, White and Wellington (2009) found that parents who intended to participate in a parenting program were more likely than non-intenders to believe that important referents (e.g., peers, spouse, family) would approve of their participation and would participate themselves. People are also more likely to engage if they have made a commitment to do so (Cialdini, 2001).…”
Section: Parent Engagement Frameworkmentioning
confidence: 99%
“…Despite extensive literature supporting the TPB, shortcomings have also been documented (Sniehotta, Presseau and Araújo-Soares 2014). Meta-analytic research has illustrated the subjective norm-intention correlation to be weaker than the attitude-intention and perceived behavioural controlintention relationships (McEachan et al 2011), leading researchers to argue that the construct does not effectively capture the impact of social influences on behaviour (White and Wellington 2009). Ajzen (1991Ajzen ( , 2015 suggests that the TPB is open to the inclusion of additional variables if they are theoretically and empirically relevant to the behaviour being investigated.…”
Section: The Theory Of Planned Behaviourmentioning
confidence: 99%